Synthesis, Molecular Docking and Evaluation of 3-4-[2-amino-4-(substitutedphenyl)-2H-[1, 3] oxazin/thiazin-6-yl 2-phenyl-3H-quinazolin-4-one Derivatives for their Anticonvulsant Activity - Jain, Nimisha; Jaiswal, Jugnu; Pathak, Ashish; Singour, Pradeep K. (Central Nervous System Agents in Medicinal Chemistry, 2018)
Background: According to the WHO, around 50 million people worldwide are suffering from epilepsy. It is due to the repeated occurring of seizures. These seizures are caused by sudden which may vary from a brief lapse of attention or muscle jerks, to severe and prolonged convulsions. Objectives: The aim of the present work was to synthesize 2-phenyl substituted quinazolinone derivatives and to evaluate them for anticonvulsant and neurotoxic activity. Methods: A series of novel 3-4-[2-amino-4-(substitutedphenyl)-2H-[1.3] oxazin/thiazin-6-yl 2- phenyl-3H-quinazolin-4-one derivatives were synthesized and evaluated for their anticonvulsant activity. The structures of the compound have been confirmed by spectral analysis. The molecular docking was performed for all the synthesized compounds to assess their binding mode to Gamma- aminobutyric acid type A (GABAA) receptor in order to rationalize their anticonvulsant activities in a qualitative way. Anticonvulsant activities of compounds were screened by using (Maximal electroshock) MES induced seizures and subcutaneous pentylenetetrazole (scPTZ) induced seizure models in Wistar rats of either sex. None of the compounds demonstrated any sign of neurotoxicity. Result: Compounds 3-4-[2-amino-4-(4-nitro-phenyl)-2H-[1, 3] oxazin-6-yl 2-phenyl-3H-quinazolin- 4-one (5a) have shown significant activity against tonic seizure by the MES model and 3-4-[2-amino- 4-(4-nitro-phenyl)-2H-[1, 3] thiazin-6-yl 2-phenyl-3H-quinazolin-4-one (5d) against clonic seizure by scPTZ induced seizure model. Conclusion: All the newly synthesized compounds had significant anticonvulsant activity. The same two compounds 5a and 5d showed promising activity, while the other compounds have moderate activity. The proposed work is to effort towards the development and identification of novel molecules as anticonvulsant agents by the synthesis of some novel quinazolinone derivatives with improved biological activity.
Keywords: MES